2012
DOI: 10.4049/jimmunol.1103377
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cell-Derived Hypoxia-Inducible Factor Attenuates Inflammation in Unilateral Ureteral Obstruction-Induced Kidney Injury

Abstract: Renal fibrosis and inflammation are associated with hypoxia, and tissue pO2 plays a central role in modulating the progression of chronic kidney disease. Key mediators of cellular adaptation to hypoxia are hypoxia-inducible factor (HIF)-1 and -2. In the kidney they are expressed in a cell type-specific manner; to what degree activation of each homolog modulates renal fibrogenesis and inflammation has not been established. To address this issue, we used Cre-loxP recombination to activate or to delete both Hif-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 74 publications
5
88
2
Order By: Relevance
“…However, the presence of myeloid HIF-αs does not alter renal fibrosis. The authors suggest that hypoxia and/or myeloid HIF-α activation alleviates renal inflammation via suppression of Ccr2 and Ccl2, which are crucial for monocyte recruitment (157). The notion that myeloid HIF-1α regulates UUO-induced nephropathy is further supported by another study using the same LysM-Cre model; however, Tateishi and colleagues reported that myeloid HIF-1α deletion promoted renal fibrosis but did not alter macrophage accumulation in the UUO model.…”
Section: Hifs In Myeloid Cellsmentioning
confidence: 58%
“…However, the presence of myeloid HIF-αs does not alter renal fibrosis. The authors suggest that hypoxia and/or myeloid HIF-α activation alleviates renal inflammation via suppression of Ccr2 and Ccl2, which are crucial for monocyte recruitment (157). The notion that myeloid HIF-1α regulates UUO-induced nephropathy is further supported by another study using the same LysM-Cre model; however, Tateishi and colleagues reported that myeloid HIF-1α deletion promoted renal fibrosis but did not alter macrophage accumulation in the UUO model.…”
Section: Hifs In Myeloid Cellsmentioning
confidence: 58%
“…While these responses are complex and not well understood, the molecular mechanism underlying renoprotection may include increased expression of certain cytoprotective factors, oxidative stress responses, and reprogramming of glucose, energy, and adenosine metabolism as well as beneficial effects on mitochondrial O 2 utilization and ROS production (9,45,48,51,52). Under certain conditions, these protective effects may be offset by injury-promoting effects ascribed to HIF activation; e.g., chronic HIF activation in tubular epithelial cells has been shown to promote fibrosis via the induction of ECMmodifying and lysyl oxidase genes (21).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, animal models of CKD support both renoprotective and injury-promoting roles (21,(44)(45)(46)(47). A major challenge has been the identification of cell types and molecular targets that mediate HIF-induced renoprotection.…”
Section: Figurementioning
confidence: 99%
“…Hct, rbc, Hb, serum EPO level, and reticulocyte counts were determined as described previously (50). For the isolation of renal PDGFRB-expressing interstitial cells, kidneys were digested as previously described (53), and cells were purified by immunomagnetic bead separation using antibodies directed against PDGFRB (catalog 14-1402-82; eBioscience) and anti-rat IgG microbeads (catalog 130-048-502; Miltenyi Biotec).…”
Section: Methodsmentioning
confidence: 99%